NON-OPIODERGIC LIKE MECHANISM FOR ANTINOCICEPTIVE ANALGESIC AND ANTIPYRETIC ACTIVITY OF ETHANOLIC ROOT EXTRACT OF OPERCULINA TURPETHUM IN SWISS ALBINO MICE - VEENA SHARMA; MANU SINGH (International Journal of Pharma and Bio Sciences, 2013)
Non-opioid analgesics including both selective and non-selective cyclooxygenase (COX) inhibitors and acetaminophen are the most widely used treatments for pain. Inhibition of COX is thought to be largely responsible for both the therapeutic and adverse effects of this class of drugs. So it is necessary to find some of the alternate effective measures. The root extract of Operculina turpethum has been used as an anti-inflammatory,purgative,hepato-protective agent and antipyretic.The present study was done to evaluate the analgesic activity of the root extract of this plant by acetic acid writhing method, formalin test, hot plate method and tail flick method along with the antipyretic potential.Oral administration of O. turpethum extract at the doses of 250,300 and 350 mg/kg b.wt. significantly decreased the number of contortions, stretchings and licking activity in pain induced mice in comparison to standard drug.The present findings indicated that Operculina turpethum possesses genuine antiinflammatory and antinociceptive properties, lending pharmacological support to folkloric or anecdotal use of the plant in the treatment and management of painful inflammatory conditions.